GRAIN SIZE IN SEDIMENTS FROM LAKE SUGAN: A POSSIBLE LINKAGE TO DUST STORM EVENTS AT THE NORTHERN MARGIN OF THE QINGHAI-TIBETAN PLATEAU - Qiang M.; Chen F.; Zhang J.; Jin M.; Zhou A.; Xiao S.; Zu R. (My University, 2007)
Samples of surface deposits in the Lake Sugan catchment, as well as surface lake sediments, eolian materials occulted in the lake ice cover, and airborne dust were collected for grain-size analysis. The results show that the coarse fraction of the lake sediments could be transported by ambient winds and to a lesser extent by river flow in the study area. Sediment cores were retrieved from Lake Sugan in December 2000, and 210Pb and 137Cs dating and grain-size analyses were performed on these samples. 210Pb ages and the volume percentage of the fraction of lake sediments >63 μm were used to reconstruct the dust storm history from 1957 to 2000. Observational data for dust storm events collected at a local meteorological station largely agrees with the reconstructed trend for the past 44 years, suggesting that lake sediments can be employed to trace the dust storm history of the northern Qinghai-Tibetan Plateau. © 2006 Springer-Verlag.
Keywords: DUST STORM; GRAIN SIZE; LAKE SEDIMENT; LAKE SUGAN